The importance of education in the education of preschool children - Achilov Obid Muzrobovich; Choponkulova Sitora Bozorovna; Egamberdiyeva Asilabonu Olimovna (Genius Journals, 2022)
The family plays an important role in preparing a child for school. Raising a child is a difficult and complex task that requires all members of the family to have a high sense of responsibility for the fate of the children. In preparing a child for school, it is good to combine all aspects of education, including spiritual, moral, mental, aesthetic, physical and labor.This article discusses about the importance of education in the education of preschool children
Keywords: Preschool education; institutions; raising child; aspects